ANALISIS KESALAHAN GRAMMATIK YANG DIBUAT OLEH SISWA KETIGA PROGRAM STUDI INGGRIS UNIVERSITAS RIAU MENULIS SEBUAH ESAI ARGUMENTATIF - Firman, Hibban; Jismulatif, Jismulatif; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive study aims to find out the grammatical errors, and the most frequent error made by the third year students of English study program Universitas Riau in writing an argumentative essay. The population of this study was the third year students of English study program Universitas Riau in the academic year 20174/2018. The third semester students were consisted of 90 as the population in this research. Thirty (30) students were taken as the sample. The method used in this research is a descriptive method. The data were collected using a written test, and were analyzed by using using Error Analysis Technique. The research findings reveal that the grammatical errros occurred were Subject verb agreement, Verb tense and form, Word order, Plurality, Preposition, Articles, Passive voice, and Auxiliary; the most frequent error was in Subject-Verb Agreement with 127 (29%) frequency.Keywords: Grammar, Error, Errors Analysis, Argumentative Essay